Modelling effects of edge density fluctuations on electron-cyclotron current drive used for neoclassical tearing mode stabilization. (14th January 2021) - Tsironis, C.; Papagiannis, P.; Bairaktaris, F.; Valvis, S. I.; Hizanidis, K.
Abstract : In this work we study the undesired effects of electron density fluctuations (in the form of blob structures which may exist in the edge region of tokamak plasmas) to the electron-cyclotron wave propagation and current drive in connection to the efficiency of neoclassical tearing mode stabilization. Our model involves the evaluation of the driven current in the presence of density perturbations, by using a combination of a wave solver based on the transfer matrix and electromagnetic homogenization methods for the propagation part prior to and inside the region of these structures (where standard asymptotic propagation methods may not be valid due to the short-wavelength limit breakdown), with a ray tracing code including island geometry effects and current drive computation for the propagation past the perturbed region. The computed driven current is input into the modified Rutherford equation in order to estimate the consequences of the wave deformation (driven by the density fluctuations) to the mode stabilization.